2017
DOI: 10.1177/0363546517707207
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Surgery After Revision Anterior Cruciate Ligament Reconstruction: Rates and Risk Factors From a Multicenter Cohort

Abstract: Background While revision ACL reconstruction (rACLR) can be performed to restore knee stability and improve patient activity level, outcomes after these surgeries are reported to be inferior to primary ACL reconstruction. Further reoperation after rACLR can have an even more profound effect on patient satisfaction and outcome. However, there is a current lack of information regarding the rate and risk factors for subsequent surgery after rACLR. Purpose To report the rate of reoperation, procedures performed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…An overall reoperation rate of 11% after revision ACL-R has been reported by the MARS group. Meniscal, revision ACL-R, and cartilage procedures accounted for 27%, 19%, and 17%, respectively, in the MARS cohort [ 33 ]. Interestingly, another study by the MARS group demonstrated that patients undergoing more than two revision ACL-Rs are 4.7 times more likely to require subsequent surgery compared to patients undergoing a first-time revision ACL-R [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…An overall reoperation rate of 11% after revision ACL-R has been reported by the MARS group. Meniscal, revision ACL-R, and cartilage procedures accounted for 27%, 19%, and 17%, respectively, in the MARS cohort [ 33 ]. Interestingly, another study by the MARS group demonstrated that patients undergoing more than two revision ACL-Rs are 4.7 times more likely to require subsequent surgery compared to patients undergoing a first-time revision ACL-R [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that graft failures in youth exceed those of the general population. 19 , 27 , 28 , 29 , 30 However, there are limited data comparing outcomes by type of hamstring autograft reconstruction technique, based on physeal status, within pediatric populations. 25 Much of the existing data report on outcomes of individual techniques.…”
mentioning
confidence: 99%
“… 49 However, the MARS group has reported higher rates of reoperation after 2-stage revision (odds ratio = 1.93) compared with single-stage revision, and higher rates of another ACL graft rupture (5% vs 2%), although neither finding was statistically significant. 14 In the current study, 4 of 32 patients met the criteria (based on radiography and magnetic resonance imaging) for bone grafting and underwent a 2-stage technique; 1 of these patients had revision graft failure at <2 years after completion of her 2-stage revision. No literature is available addressing bone tunnel grafting in the pediatric population; this may be explained by the adjustment of tunnel placement upon revision in the pediatric population, which may be less common in the adult population.…”
Section: Discussionmentioning
confidence: 89%